Implementasi Kompetensi Kepribadian Guru Pendidikan Agama Islam Dalam Pembentukan Karakter Toleransi Beragama Siswa Di SMA Swasta Sri Langkat Tanjung Pura - Siti Nadhrah; Ahmad Sanusi Lukman; Diani Syahfitri (Yayasan Rahmat Islamiyah, 2022)
The purpose of this study was to find out how the implementation of the personality competencies of Islamic religious education teachers in the formation of students' tolerance character at the Sri Langkat Tanjung Pura Private High School. The research approach uses a qualitative approach with a descriptive method. Data was collected by observation, interviews, and documentation. The results showed that Islamic religious education teachers at Sri Langkat Private High Schools had quite good personalities. The personality competencies that must be possessed by an Islamic Religious Education teacher are having a disciplined personality, an honest and fair personality, having commendable character, being a role model, having a stable personality, and having an authoritative personality. The condition of the religious tolerance character of students at Sri Langkat Private High School can be said to be quite good. Students make friends with friends of different religions and there has never been a religious conflict at the school. There are two factors that influence the formation of the character of religious tolerance of students at the Sri Langkat Tanjung Pura Private High School, namely internal and external factors. Where external factors are from the students themselves, namely being able to control emotionally on themselves and also external factors where the student's living environment greatly influences the formation of the character of religious tolerance which includes the school environment, family and society.